Cardiac Pacemaker - Zapata Uribe, Pedro; Abreu, Phillipe; Andrade, Rubens Ramos de [UNESP]; Tofano de Barros, Rubens; Felicio, Marcello Laneza [UNESP]; Brenner Affonso da Costa, Ana Cláudia (Springer Nature, 2025)
Pacemakers are artificial cardiac stimulation devices that control the heart rate by stimulating the myocardium. The goal of this system is to guarantee an appropriate heart rate according to physiological needs, in addition to synchronizing the beating of the atria with the ventricles.